UPAYA MENINGKATKAN KETERAMPILAN MENGAJAR GURU BERBASIS MODEL PEMBELAJARAN TEAM GAME TOURNAMENT MELALUI BIMBINGAN BERKELOMPOK DI SDN 016 BANJAR LOPAK - Bartunus Bartunus (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to improve teacher teaching skills based on team game tournament learning models through group guidance. This research was conducted in September - October 2019 at SDN 016 Banjar Lopak with 14 subjects as teachers. The study design uses school action research that has stages of planning, implementation, observation, and reflection. The research instrument used observation sheets. The results showed an increase in teacher teaching skills based on team game tournament learning models in the first cycle by 71% which is enough to be 87% which is included in the excellent category. Based on the results and discussion it can be concluded that through group counselling can improve teacher teaching skills based on team game tournament learning models.